Defective iron homeostasis in lysosomal storage diseases - Chen, C; Chun-Wu Chen (2013)
Niemann-Pick type C1 (NPC1) disease is a neurodegenerative lysosomal storage disorder characterized by the accumulation of multiple lipids in the late endosome/lysosomal system and reduced acidic store calcium levels. Since the lysosomal system is involved in regulating aspects of transition metal ion homeostasis and its intracellular compartmentalization, we have investigated whether there are metal ion metabolism defects and haematological abnormalities in NPC1 disease. We have identified multiple haematological changes, including decreased haematocrit, haemoglobin and mean corpuscular haemoglobin volume in Npc1-/- mice. Similar haematological changes with low normal serum iron levels as well as low normal haematocrit, haemoglobin, mean corpuscular volume and mean corpuscular haemoglobin were observed in NPC1 patients, suggesting that NPC1 patients are at risk of iron deficiency. Furthermore, decreased levels of serum iron, transferrin saturation, elevated levels of serum copper and ceruloplasmin and up-regulated expression of soluble transferrin receptor (s-TfR), ferritin levels in Npc1-/- mice and NPC1 patients were observed. Additionally, up-regulation of hepatic transferrin receptor, down-regulation of hepatic hepcidin and altered expression of multiple copper and zinc transporters were also found in Npc1-/- mice. These data demonstrate that systemic metal dyshomeostasis, intracellular metal compartmentalization defects and impaired erythropoiesis occur in NPC1 disease. As transition metal dyshomeostasis may be involved in the pathogenesis of NPC1 disease, we hypothesized this may represent a novel therapeutic intervention point for adjunctive therapy. To test this hypothesis, we have evaluated several metal manipulation treatments, including metal supplementation, metal chelation and metal ionophore treatments, in Npc1-/- mice. Our results revealed that (i) iron supplementation, (ii) reduced copper absorption reagent (iii) and copper/zinc ionophore therapies significantly either improved haematological abnormalities, neurological/motor functions or survival in Npc1-/- mice. These data suggest that metal-targeted therapies may be useful adjunctive therapies in NPC1 disease patients.